Institutionalising Design Excellence in Central Sydney 1988-2000 - Freestone, Robert; Davison, Gethin; Hu, Richard; Baker, Sarah (International Planning History Society Proceedings, 2016)
High-quality architectural and urban design are now widely regarded as key contributors to the competitive advantage of global cities. Sydney, Australia is no exception. Since 2000 ‘design excellence’ has become a central mantra applied to improve design quality. Focusing on the jurisdiction of Sydney City Council, this paper identifies an assemblage of three threads from which design excellence (and in particular mandatory competitive design processes) emerged as a planning objective in the late 20th century. Deep into the post-war period, local government planning processes were still enmeshed in a statutory land use planning system based on a traditional town and country planning paradigm. From the late 1980s these processes were challenged by newer understandings of the ‘design dividend’ rewarding competitive global cities within an emerging neo-liberal rubric. From 2000 Sydney CBD’s touchstone of design excellence has required all major developments on privately-owned sites to undergo a competitive design process. This mandatory step in development approval procedures is unique for an Australian local authority if not globally. By unpacking the evolution of this modern competitive design-injected planning process, we gain better historic insights into localised governance responses and their consequences in the context of the neo-liberal global city.